Psykisk ohälsa bland studenter - Kazan, Ibrahim (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
Mental illness among young people is generally something that has tripled in the 2000s. Thisform of mental illness is usually expressed in the form of stress, anxiety and depression.(Socialstyrelsen, 2013) The group of young people who appear to be most exposed to thisconsists of students (Socialstyrelsen 2017; Folkhälsomyndigheten 2018).The purpose of this study was to be able to measure how widespread mental illness really isamong students through an interview with the school curator at Luleå University ofTechnology and a survey to find out why mental health is so prevalent among student.The questions that were prepared for both the survey and the interview with the curator areclosely linked, although the interview is more in-depth.The questions raised in the study were, have you ever experienced mental illness during yourstudy period and whether the students have experienced anxiety or stress. Consequently, thestudents had to answer what the causative factors were, as well as what the students do to bestrecover.The results of the study indicate that almost half of the students (47%) have experiencedmental illness during their studies. However, it is interesting that as many as 32 people (89%)responded that they had experienced the feeling of stress and anxiety during their studies. 32people (64%) of the students who thought they were experiencing stress and anxiety felt thatit was due to the studies.When asked what the students do to recover from mental illness or anxiety no one (0%)answered that they seek professional support in the form of a psychologist or student healthconsular. A bit over half of the people asked (58%) deal with it on their own while one of four(25%) choose to do nothing at all and let it pass. The results of the interview and surveys areto a large extent consistent.Mental illness is a fact among students at the same time as it is a major threat to positivedevelopment in society. The numbers are frightening both when it comes to the number ofstudents who are affected and when it comes to ...